Fur-seal, sea otter, and salmon fisheries [electronic resource] : acts of Congress, President's proclamations, regulations governing U.S. vessels, acts of Parliament, orders in council, pertaining to the fur-seal fisheries in Bering Sea and north Pacific Ocean, sea otter regulations, laws as to salmon fisheries in Alaska. (Washington : G.P.O., 1896)
Running title: Fur-seal fisheries in Bering Sea. Cover title. "Treasury Department, document no. 1850, Office of Division of Revenue Cutter Service" -verso of t.p. Includes index. Electronic reproduction. Mode of access: Internet. 44